From the International Patient Safety Goals to Mexico’s Essential Actions for Patient Safety: A Narrative Policy Review - Anayeli González-Bravo; Adolfo Sánchez-Flores; Emma Virginia Herrera-Huerta; Elena de la Cruz Herrera-Cogco; Guadalupe López-Vásquez; Olga Lidia Valenzuela-Limón; Raymundo Escutia-Gutiérrez; Jorge Luis Ramos-Cabrera; Jorge Alfonso Santos-Rosas (Hygiene, 2026)
Patient safety policies in Mexico have evolved through the incorporation and adaptation of the International Patient Safety Goals (IPSG) within the broader Essential Actions for Patient Safety (AESP) framework. This narrative policy review aimed to analyze this evolution, compare the main characteristics of both frameworks, and examine the available evidence concerning AESP implementation and current challenges in Mexico. A structured literature search was conducted between March and July 2026 in PubMed and SciELO, supplemented by Google Scholar and official sources from the World Health Organization and Mexican health authorities; the final search update was performed in July 2026. The narrative synthesis included 26 sources: 17 scientific or academic publications and nine official or institutional documents. The evidence indicates that the AESP retained the six principal clinical safety areas of the IPSG while adding incident reporting and analysis and patient safety culture as organizational components. However, available Mexican empirical evidence is limited and does not establish national implementation levels or demonstrate that the AESP have independently reduced adverse events or improved patient outcomes. Further national, multicenter, longitudinal, and comparative evaluations are needed to assess implementation, adherence, reporting performance, safety culture, and patient outcomes.